South Korea's Mobility Diplomacy towards Indonesia: Analysis of the Visa free Policy as a Diplomatic Communication Strategy - Hashbi Ashshidiq; Yuka Maya Nirwana (Journal of Social Research, 2026)
Bilateral relations between South Korea and Indonesia have developed significantly in the fields of economy, culture, and tourism. One of the policies attracting attention is the visa-free policy for Indonesian citizens visiting South Korea, particularly through Jeju Island. This policy not only aims to increase tourist arrivals but also functions as an instrument of public diplomacy to strengthen people-to-people relations between the two countries. This study aims to analyze how the visa-free policy is positioned as a public diplomacy communication strategy of South Korea toward Indonesia. The research employs a qualitative approach using a single case study design. Data were collected through document analysis of official South Korean government documents, Korea Tourism Organization reports, embassy press releases, and Indonesian media coverage during the 2014–2024 period. Data analysis techniques include thematic analysis, framing analysis, and discourse analysis to identify the diplomatic communication meanings embedded in the policy. The findings indicate that the visa-free policy functions as a message of openness, a soft power instrument, and a mechanism for strengthening interactions between the societies of both countries. The policy also expands cross-border communication through the involvement of non-state actors such as tourism industries and cultural communities. In conclusion, the visa-free policy is not merely an immigration regulation but an effective public diplomacy strategy in building a positive image of South Korea in Indonesia.